HELICOBACTER PYLORI INFECTION IN PRIMARY AUTOIMMUNE ADRENAL INSUFFICIENCY: A CROSS-SECTIONAL ANALYTICAL STUDY - Sahoo, Jayaprakash; Venkatesh, S.; Naik, Dukhabandhu; Mohan, Pazhanivel; Pandit, Nandini; Kamalanathan, Sadishkumar; Kar , Sitanshu Sekhar (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Helicobacter pylori (H. pylori) is a common infectious bacterium that colonizes the stomach in approximately 50% of the world population. Because of its ability to elicit a chronic immune response in the host, studies have suggested a possible role for H. pylori in the development of various autoimmune diseases. The primary objective of our study was to compare the proportion of H. pylori infection between patients with primary autoimmuneadrenal insufficiency and healthy controls. The secondary objectives were to determine the effect of H. pylori treatment on plasma ACTH levels and inflammatory parameters (erythrocyte sedimentation rate, high sensitivity C-reactiveprotein, and interleukin-6) in patients with primary autoimmune adrenal insufficiency. METHODOLOGY A total of 62 subjects (31 cases and 31 healthy controls) were recruited in this study. A patient was diagnosed to have autoimmune primary adrenal insufficiency if he haslow serum cortisol, plasma ACTH >100 pg/ml, normal or reduced adrenal volume without calcification on noncontrast computerized tomography scan, and absence of secondary conditions causing adrenal insufficiency. Both the patients and healthy controls underwent a 14C urea breath test for detection of H. pylori infection. RESULTS The age, gender, weight, body mass index, and waist circumference were similar across the two groups. The proportion of H. pylori infection was significantly higher in subjects with autoimmune primary adrenal insufficiency 9/31 (29.1%) compared to healthy subjects 2/31 (6.4%) [p = 0.02]. In our study, both H. pylori positive and negative patients had comparable plasma ACTH and inflammatory markers at baseline. Additionally, there was no change in either plasma ACTH or inflammatory parameters after treatment for H. pylori infection. CONCLUSION The patients with autoimmune primary adrenal insufficiency have a markedly increased prevalence of H. pylori infection. Future studies are required to look for the cause-and-effect relationship between these two diseases.